Production management model for waste reduction using 5S, TPM and poka yoke tools in a peanut snack manufacturing company - Aldave Vasquez, Yadhira Nicole (2025)
This research project addresses the challenges of waste in a Small and Medium-sized Enterprises (SME) dedicated to the production of peanut snacks in Peru. Production waste, a persistent problem in production processes, has negatively impacted the company's operational efficiency and profitability. To overcome this problem, three fundamental engineering tools will be implemented: 5S, Informative Poka Yoke and Total productive maintenance (TPM). The 5S methodology will be used to redefine and optimize work spaces, promoting organization and discipline at each stage of the production process. Informational Poka Yoke systems will be introduced to prevent and correct errors in real time, reducing the generation of production waste and improving consistency in the quality of the final product. Additionally, the TPM methodology focuses on reducing production waste in processes that involve machinery, using a simulator to address failures of said equipment The main objective of this project is to significantly reduce waste in the production of peanut snacks, simultaneously improving the overall efficiency of the processes and guaranteeing high quality standards. The results obtained after the application of the three tools were positive. In the final 5S audit, an increase in the score was achieved, going from 37.6% in the initial stage to 90.4% in the final. The results of the Poka Yoke template showed reduced error rates: 4.25% in selection process, 2.86% in toasting and 2.73% in the semitoasting. In the TPM simulator the availability of the machine was 98.45%. These achievements demonstrate the effectiveness of the strategies implemented in improving the efficiency and profitability of the production of peanut snacks in the SME company